Bifunctional colorimetric biosensors via regulation of the dual nanoenzyme activity of carbonized FeCo-ZIF - Wu, Tengteng; Ma, Zhangyan; Li, Peipei; Lu, Qiujun; Liu, Meiling; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo (Sensors and actuators. B, Chemical, 2019)
•FeCo alloy doped carbon sphere (FeCo@C) was obtained from the carbonization of FeCo-ZIF.•FeCo@C exhibits satisfactory mimetic dual-enzyme activity.•The mimetic dual-enzyme activity can be controlled and used as bifunctional colorimetric biosensor for HQ and H2O2.•The FeCo@C solves the defect of instability of non-precious metal nanoparticles owing to the protection of C sphere.•The FeCo@C has strong magnetic which could achieve multiple recycling. Extensive attention has been paid to rationally control the artificial nanoenzyme activities via suitable strategies to prepare various nanoscale functional materials. Herein, FeCo co-doped carbon sphere (FeCo@C) with intrinsic oxidase-like and peroxidase-like activity has been obtained from the carbonization of FeCo-ZIF. The unique dual-enzyme catalytic property of FeCo@C can be simply regulated and utilized for bifunctional colorimetric platforms. At pH 3.6 and catalytic reaction time of 6 min, the FeCo@C possesses strong oxidase-like activity which can catalytically oxidize 3,3′,5,5′-tetramethylbenzidine (TMB) owing to the production of O2·− with the participation of O2 to result in typical color change of the system. Hydroquinone (HQ) as a reducing agent can induce the color fading, and therefore, a novel colorimetric biosensing platform for HQ was constructed with the linear range of 1–30 μM and detection limit of 0.8 μM. However, with the pH of 4.4 and catalytic reaction time of 3 min, the oxidase-like activity of FeCo@C was obviously weakened, and the peroxidase-like activity of FeCo@C is still high. Hence, a facile analytical method was developed to detect H2O2 based on the peroxidase-like activity of FeCo@C with the linear range of 1–240 μM and detection limit of 1 μM. Moreover, the FeCo@C has high stability and strong magnetism with the activity being kept well after several cycles of recycling, which shows great prospect in biosensing and catalysis areas.